Effects of the Combination of Chemical Pretreatments and Dry Grinding of the Arundo donax L. Plant - Patricia O. Schmitt; Débora da S. Rodrigues; Matheus de P. Goularte; Silvia H. F. da Silva; Marcilio M. Morais; Darci A. Gatto; Cláudia F. Lemons e Silva; Camila M. Cholant; André L. Missio (Macromol)
Arundo donax L. is a plant with great potential as lignocellulosic biomass, being a promising source for the development of biodegradable materials. This study evaluated the effects of different chemical pretreatments (H2SO4, NaOH, and NaClO) combined with dry milling on the physicochemical properties of biomass. Pretreatment with NaClO was the most effective in removing lignin, reducing its content to 0.2%, while increasing the cellulose content to 67%. Pretreatment with H2SO4, although retaining a higher lignin content (24%), resulted in the greatest reduction in particle size, reaching a mean diameter (Dm) of 44.31 µm after 20 h of milling. Density analysis revealed that the raw samples reached a maximum density of 0.218 g/cm3 after 20 h of milling, with the pretreated samples showing lower densities due to the removal of structural components. Thermal analysis showed mass losses of up to 66.4% for samples pretreated with NaClO after 10 h of milling, indicating significant structural changes and improved thermal stability. Morphological analysis via SEM demonstrated elongated and fine particles, with acid pretreatment resulting in the most pronounced structural changes. These findings highlight the efficiency of combining chemical and physical pretreatments to modify the structure of A. donax L., optimizing its properties for the production of high-performance biodegradable materials.